The Nature of Verbal Short-Term Impairment in Dyslexia: The Importance of Serial Order - Majerus, Steve; Cowan, Nelson (Frontiers in Psychology, 2016)
Verbal short-term memory (STM) impairment is one of the most consistent associated deficits observed in developmental reading disorders such as dyslexia. Few studies have addressed the nature of this STM impairment, especially as regards the ability to temporarily store serial order information. This question is important as studies in typically developing children have shown that serial order STM abilities are predictors of oral and written language development. Associated serial order STM deficits in dyslexia may therefore further increase the learning difficulties in these populations. In this mini review, we show that specific serial order STM impairment is frequently reported in both dyslexic children and adults with a history of dyslexia. Serial order STM impairment appears to occur for the retention of both verbal and visuo-spatial sequence information. Serial order STM impairment is however not a characteristic of every individual dyslexic subject and is not specific to dyslexia. Future studies need to determine whether serial order STM impairment is a risk factor which, in association with phonological processing deficits, can lead to dyslexia or whether serial order STM impairment reflects associated deficits causally unrelated to dyslexia.